The effect of nanoparticle uptake on cellular behavior: disrupting or enabling functions? - Miserocchi G (Dove Medical Press, 2012)
Alice Panariti, Giuseppe Miserocchi, Ilaria RivoltaDepartment of Experimental Medicine, University of Milano Bicocca, Monza, ItalyAbstract: Nanoparticles (NPs) are materials with overall dimensions in the nanoscale range. They have unique physicochemical properties, and have emerged as important players in current research in modern medicine. In the last few decades, several types of NPs and microparticles have been synthesized and proposed for use as contrast agents for diagnostics and imaging and for drug delivery; for example, in cancer therapy. Yet specific targeting that will improve their delivery still represents an unsolved challenge. The mechanism by which NPs enter the cell has important implications not only for their fate but also for their impact on biological systems. Several papers in the literature discuss the potential risks related to NP exposure, and more recently the concept that even sublethal doses of NPs may elicit a cell response has been proposed. In this review, we intend to present an overall view of cell mechanisms that may be perturbed by cell–NP interaction. Published data, in fact, emphasize that NPs should no longer be viewed only as simple carriers for biomedical applications, but that they can also play an active role in mediating biological effects.Keywords: nanoparticles, uptake, intracellular trafficking, bio compatibility